Ongoing and evolving clinical trials enhancing future colorectal cancer treatment strategies. (4th March 2022) - Ros, Javier; Saoudi, Nadia; Salvà, Francesc; Baraibar, Iosune; Alonso, Guzman; Tabernero, Josep; Elez, Elena
ABSTRACT: Introduction: Molecular profiling has led to significantly longer survival in metastatic colorectal cancer (CRC) patients. Clinical guidelines recommend testing for KRAS/NRAS, BRAF, and MSI status, and over the last few years, several promising new biomarkers have also been identified. Circulating tumor DNA has reshaped the prognosis of localized CRC. These genomic findings can guide treatment management to improve clinical outcomes. Areas covered: Preclinical and clinical data over the last decade were reviewed for known and novel biomarkers with clinical implications in refractory and metastatic CRC. In the localized stage, all clinical trials involving new approaches such as liquid biopsy or neoadjuvant immunotherapy are also discussed. Molecular alterations and targeted agents are described, and data from completed and ongoing studies with targeted therapy and immunotherapies are presented. Expert opinion: The implementation of liquid biopsies in the localized CRC setting has reshaped management of this disease. The expanded use of biomarkers to guide CRC patients' treatment has revealed a level of complexity arising from interactions between different biomarkers. Prevalence of most established targetable biomarkers is low; however, the number of identified biomarkers in CRC is increasing. Thus, metastatic CRC may ultimately be considered an umbrella diagnosis encompassing numerous rare disease subtypes.